Improving School Image and Parents' Interest in Choosing Schools Influenced by Product, Promotion and Pricing Strategies in Elementary Schools: Peningkatan Citra Sekolah Serta Minat Orang Tua Siswa Untuk Memilih Sekolah yang Dipengaruhi oleh Strategi Produk, Promosi dan Harga Pada Sekolah Dasar - Sulchan, Kusnaini; Rizal, Hadiah Fitriyah (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this thesis research is to find out and analyze the product, promotion and price affect the school's image, influence the parents' interest in choosing the school and to find out and analyze the school image as a mediator variable capable of influencing the relationship between product, promotion, price and parents' interest in choosing a school. schools at SD Muhammadiyah 5 Porong. This research belongs to the type of quantitative research and uses descriptive statistical analysis. Researching on a particular population or sample. Data collection with a limited questionnaire method. Respondents are the guardians of the students of SD Muhammadiyah 5 Porong as many as 125 people. Validity test analysis. It is necessary to test the validity and reliability of the researcher's information using the W-Start program. .Analysis of hypothesis testing on the relationship between variables should be carried out using path analysis assisted by the SPSS type 21 windows program. The results of the SPSS program analysis show that the influence of the Product, Promotion and Price aspects together in producing School Image is 65%. Meanwhile, the other 35% of m is influenced by other aspects.